Understanding and analyzing competitive dynamics : methods, processes, and applications to a regional setting - Arik, Murat; Livingston, Steven Greene (Lexington Books, 2014)
Understanding and Analyzing Competitive Dynamics will serve as the first book for economic development professionals, undergraduate and graduate students, and businesses because it answers the following three questions: What are the tools and techniques to analyze regional dynamics, how can these tools be used in a regional setting, and how can these tools help us formulate new directions? The book also highlights the necessity of regional level leadership in leveraging existing regional assets to create a cluster-based competitive regional economy through regional-level marketing, increasing synergy between industries in target clusters and their suppliers and customers, strengthening the cluster supply-chain by diversifying target clusters, and investing in human resources.--Provided by publisher.